Tác động của bất định chính sách tiền tệ đến chi phí sử dụng vốn của doanh nghiệp: Trường hợp các công ty niêm yết tại Việt Nam - Hoàng Việt, Huy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
As Vietnam continues to deepen its integration into the global economy, monetary policy has become increasingly difficult to predict amid ongoing macroeconomic volatility. This study examines the impact of monetary policy uncertainty on the cost of capital of Vietnamese firms. Using fixed-effects regressions on a panel of listed non-financial companies, the results show that monetary policy uncertainty significantly increases firms’ cost of capital, reflected in both the cost of debt and equity. These findings remain robust across various alternative robustness checks. Moreover, local institutional quality, particularly transparency, time cost, and informal charges, plays a moderating role in this adverse effect. These results highlight the importance of considering the cost of capital implications of monetary policy and the necessity of improving the business environment to create stable conditions for firms to grow.